Indirect Pulse-vector Control of Wound Rotor Induction Motor Drive in ANSYS Electromagnetics Suite - Tatiana Andreevna Funk; Yuriy Semenovich Usynin; Evgeniy Viktorovich Belousov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper deals with the problem of estimation of rotor angular position for the indirect pulse-vector control of wound rotor induction motor drive. The paper considers issues of thematic justification and expanding of the field of using sensorless motor drives. With a view to improve energy consumption readings during design and modernization of motor drives of massive mechanisms with moderate standards for accuracy of velocity control, requiring long-term velocity decrease during load reduction (according to technological process conditions), using the system of the pulse-vector control of wound rotor induction motor is suggested. The paper provides the solution for the problem of developing math models of this motor drive system both for the motor-mounted sensor, and for indirect angular position sensing. The models were developed in ANSYS Electromagnetics Suite using the finite element method for studying electromagnetic processes. Based on the models, the investigation of transition and steady states of a motor drive was carried out, process quality parameters were obtained, namely: max and root-mean-square currents, torques; velocity control errors caused by pulse operation mode. From that simulation, the result illustrates the effectiveness of the proposed approach.